COMPREHENSIVE LEXICOGRAPHIC WORK ON COMMERCIAL AVIATION BUSINESS TERMINOLOGY - Akmaldinova, Oleksandra M.; Pysmenna, Olga O. (Proceedings of National Aviation University (archive), 2008)
Considered are the theoretical and methodological aspects of the development of comprehensive lexicographic terminological referential editions as a result of fundamental classifying work “Business English in Aviation” (in two versions: English-Ukrainian and Ukrainian-English) to be used by aviation specialists for educational and practical purposes.